2021
DOI: 10.21203/rs.3.rs-268410/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

External Validation of the 4C Mortality Score among COVID-19 Patients Visiting the Emergency Department or admitted to Hospital in Ontario, Canada

Abstract: Objectives: Risk prediction scores are important tools to support clinical decision-making for patients with coronavirus disease (COVID-19). The objective of this paper was to validate the 4C mortality score, originally developed in the United Kingdom, for a Canadian population. Methods: We conducted an external validation study within a registry of COVID-19 positive emergency department visits and hospital admissions in the Kitchener-Waterloo and Hamilton regions of southern Ontario between March 4 and Januar… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…This may represent clinical differences across each region, including patient population and the medical management of hospitalised patients with COVID-19. Nevertheless, external validation in Brazil, 6 Canada, 7 France, 8 Netherlands 9 and Pakistan 10 has demonstrated consistent performance for the 4C Mortality Score.…”
Section: Discussionmentioning
confidence: 91%
“…This may represent clinical differences across each region, including patient population and the medical management of hospitalised patients with COVID-19. Nevertheless, external validation in Brazil, 6 Canada, 7 France, 8 Netherlands 9 and Pakistan 10 has demonstrated consistent performance for the 4C Mortality Score.…”
Section: Discussionmentioning
confidence: 91%
“…But for the 1-year mortality, CCI had the highest AUROC curve (Table 2 and Figure 1d). These results were also reflected in the way in which these scores are normally used: 4CMS is used to estimate intrahospital mortality [10], and CCI is used to estimate mortality after 10 years [8]. CCI had also already shown a good predictivity in mortality at 1 year in elderly patients experiencing a first acute heart failure hospitalization [29], as well as at 1 year after having had a hip fracture [30].…”
Section: Discussionmentioning
confidence: 99%
“…It focuses on the number of comorbidities. Once two comorbidities were included, you get the maximum score [10]. The CCI takes into account more specific consideration of the impact on the gravity of each comorbidity on the total score [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 33 Comparable results have been found in studies that performed external validation in Brazil, Canada, France, the Netherlands, and Pakistan. 34 35 36 While this model has a high potential for its generalizability to patients around the world, most of the studies that have externally validated this model have only included patients admitted to the hospital, suggesting that this model is best used for predicting the mortality of hospitalized patients. Recently, a small study in Saudi Arabia performed a retrospective analysis of 506 patients diagnosed with COVID-19, which included hospitalized and outpatients, and found that the 4C Mortality score correctly estimated 95.3% of the deaths.…”
Section: Coronavirus Disease 2019-specific Scoresmentioning
confidence: 99%